The BBSome assembly is spatially controlled by BBS1 and BBS4 in human cells - Prasai, Avishek; Schmidt Cernohorska, Marketa; Ruppova, Klara; Niederlova, Veronika; Andelova, Monika; Draber, Peter; Stepanek, Ondrej; Huranova, Martina (The Journal of biological chemistry, 2020)
Bardet-Biedl syndrome (BBS) is a pleiotropic ciliopathy caused by dysfunction of primary cilia. More than half of BBS patients carry mutations in one of eight genes encoding for subunits of a protein complex, the BBSome, which mediates trafficking of ciliary cargoes. In this study, we elucidated the mechanisms of the BBSome assembly in living cells and how this process is spatially regulated. We generated a large library of human cell lines deficient in a particular BBSome subunit and expressing another subunit tagged with a fluorescent protein. We analyzed these cell lines utilizing biochemical assays, conventional and expansion microscopy, and quantitative fluorescence microscopy techniques: fluorescence recovery after photobleaching and fluorescence correlation spectroscopy. Our data revealed that the BBSome formation is a sequential process. We show that the pre-BBSome is nucleated by BBS4 and assembled at pericentriolar satellites, followed by the translocation of the BBSome into the ciliary base mediated by BBS1. Our results provide a framework for elucidating how BBS-causative mutations interfere with the biogenesis of the BBSome.
Keywords: Microscopy, Fluorescence; cilie; assembly; CRISPR-Cas systémy; Humans; protein assembly; cilium; Bardet-Biedl syndrome; podjednotky proteinů; BBSome; fluorescenční mikroskopie; mutace; Fluorescence Recovery After Photobleaching; lidé; protein sorting; Cilia; CRISPR-Cas Systems; buněčné linie; Gene Editing; Bardet-Biedl Syndrome; Cell Line; microscopic imaging; Cytoplasm; Protein Subunits; proteiny asociované s mikrotubuly; primary cilium; cytoplazma; FRAP; ciliopathy; Bardetův-Biedlův syndrom; Mutation; editace genu; genetic disease; Microtubule-Associated Proteins